Rental Discrimination in the Multi-ethnic Metropolis: Evidence from Sydney. Issue 4 (1st October 2016) - MacDonald, Heather; Nelson, Jacqueline; Galster, George; Paradies, Yin; Dunn, Kevin; Dufty-Jones, Rae
Abstract: Investigating differential treatment in rental housing markets is important to ensure that renters are not discriminated against based on their personal characteristics. However, little Australian research has focused systematically on this question. This paper reports the results of a study that used paired tests to estimate the extent of differential treatment of Anglo, Indian, and Muslim Middle Eastern renters in the Sydney metropolitan housing market. We find statistically significant differences in treatment on several measures, including the likelihood an agent will offer an individual appointment, will provide additional information about other housing, will provide additional information about completing the application form, and will contact a prospective renter after an inspection.